Strategi Menghafal Al-Qur’an bagi Generasi Z di Era Digital: Studi Kasus pada Mahasiswa UIN Madura - Fajriyah Alifatul Aulia; Saiful Arif (Research Institute and Community Engagement of UIN MADURA, 2026)
Demographically, students belong to Generation Z, which relies heavily on digital technology in various aspects of life, including memorizing the 30th chapter of the Quran as a graduation requirement for students of the Islamic Religious Education (PAI) Study Program at UIN Madura. This study focuses on the strategies for memorizing the Quran used by students in the digital era and the effectiveness of using digital media to support memorization. This study uses a qualitative approach with a case study type. Data were obtained through interviews with seven PAI students and three lecturers teaching Quran memorization, observation, and documentation. Data analysis included transcription, coding, thematic analysis, and data triangulation. The results showed that students combined traditional methods such as muraja'ah, tikrar, talaqqi, and direct deposits to lecturers with the use of digital technologies such as digital Quran applications, YouTube, audio murrotal, Google Drive, and Google Calendar. The use of digital media was considered effective in increasing memorization flexibility, assisting verse repetition, and improving tajweed through audio. The success of memorizing the Al-Quran in the digital era is influenced by students' ability to integrate technology with discipline and direct guidance from lecturers who teach Al-Quran memorization.